Fecal Microbiota Characterization of Seychelles Giant Tortoises (Aldabrachelys gigantea) Living in Both Wild and Controlled Environments - Sandri, Camillo; Correa, Federico; Spiezio, Caterina; Trevisi, Paolo; Luise, Diana; Modesto, Monica; Remy, Selby; Muzungaile, Marie-May; Checcucci, Alice; Zaborra, Cesare Avesani; Mattarelli, Paola (Frontiers in Microbiology, 2020)
A microbiome is defined as a complex collection of microorganisms and their genetic material. Studies regarding gut microbiomes of different animals have provided ecological and evolutionary information showing a strong link between health and disease. Moreover, there are very few studies which compare the gut microbiota of animals housed under controlled conditions and in a wild habitat. As concerns reptile gut microbiota, few studies have been carried out, mainly regarding carnivorous reptiles. The aim of this study was first to describe the overall microbiota structure of Aldabra giant tortoises (Aldabrachelys gigantea) and, second, to compare the microbiota of tortoises living under natural conditions and tortoises living in controlled environments, such as zoological and botanical parks, in Italy and in the Seychelles. Seventeen fecal samples were collected from giant tortoises located on Curieuse Island (CI, n = 8), at the Botanical Garden (BG, n = 3) in Mahé (Seychelles Islands) and at Parco Natura Viva – Garda Zoological Park (PNV, n = 6) in Verona (Italy). The V3-V4 region of the 16S rRNA gene was amplified in order to characterize the gut microbiota profile. Overall, the major phyla identified were Bacteroidetes 42%, Firmicutes 32% and Spirochaetes 9%. A higher microbial diversity (alpha indices) was observed for the BG samples as compared to the PNV samples (Shannon: 5.39 vs. 4.43; InvSimpson: 80.7 vs. 25; Chao1: 584 vs. 377 p ≤ 0.05). Moreover, the results in the present study showed a significant difference in beta diversity between the samples from CI, BG and PNV (p = 0.001), suggesting a different bacterial fecal profile of giant tortoises at the different habitats. This study provided novel insights into the effects of different environmental conditions on the gut microbial communities of giant tortoises. In particular, important and valuable information regarding the differences between natural and controlled environments regarding bacterial gut community structure were reported. These differences could help to drive better management of giant tortoises in controlled environments far away from their natural country.